Test Antioxidant Content In Herb Kyllinga nemoralis Extract With DPPH Method - Moh. Firmansah; Beta Herilla Sekti; Alfa Frista Arta (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Antioxidants are compounds capable of slowing or preventing oxidation, even in relatively low concentrations, thereby contributing to various physiological functions in the body. The antioxidant components found in plants act as free radical scavengers by transforming them into less reactive molecules. Jukut Pendul (Kyllinga nemoralis) contains several bioactive substances, including flavonoids, tannins, and alkaloids, which are recognized for their potential as natural antioxidants. Flavonoids, for instance, exhibit antioxidant activity by donating hydrogen atoms or through their metal-chelating properties. These compounds can be present as glycosides (with glucose moieties) or in the free form known as aglycones. This research aimed to evaluate the antioxidant capacity of Kyllinga nemoralis extract. The plant material was sourced from Banyuwangi, East Java. Extraction was performed using the maceration method with 70% ethanol as the solvent. The free radical scavenging activity was assessed using the DPPH (1 radical) method. Ascorbic acid was used as positive control. Measurement of absorbance was carried out through UV-Vis spectrophotometry. The extract was tested at concentrations of 20, 40, 60, 80, and 100 μg/mL. The findings revealed that the value of Kyllinga nemoralis extract was 11.351 μg/mL, whereas ascorbic acid exhibited an IC50 of 3.43 μg/mL. The antioxidant activity of Kyllinga nemoralis ethanol extract falls into the very strong category, ranging <50-100 μg/mL. These results suggest that although the antioxidant strength of Kyllinga nemoralis is lower than that of , the extract still possesses detectable radical-scavenging activity.